Faktor-faktor yang Mempengaruhi Investment Decision pada Karyawan Swasta di Jabodetabek - Pangaribuan, Meiko Andreas; Bertuah, Eka (Neolectura, 2023)
This research aims to determine the effect of financial literacy on financial risk tolerance, financial behavior, and investment decisions among private employees in Jabodetabek. Additionally, this research also aims to identify the influence of financial behavior on investment decisions, as well as the mediating role of financial risk tolerance and financial behavior in connecting the influence of financial literacy on investment decisions. The analysis method used in this study is structural equation model (SEM). The research results show that influence, financial literacy has an effect on risk tolerance, financial behavior and Investment decisions. Financial behavior does not have effect on investment decisions. Risk tolerance has an effect on financial behavior and investment decisions, and there is a partial mediating risk tolerance in connecting the influence of financial literacy on investment decisions. However, the research results also show that financial behavior does not play a partial mediator of the influence of financial literacy on investment decisions. This research is expected to provide an empirical contribution to the theory Behavioral Finance is the existence of financial behavior which refers to the actions and decisions taken by individuals related to financial management.